PENGEMBANGAN TES DIAGNOSTIK THREE TIER MENGGUNAKAN MICROSOFT EXCEL TENTANG FLUIDA DINAMIS DI SMA - Putra, Yoga Harisyah; Maria, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to develop a three tier diagnostic test using microsoft excel about dynamic fluid. The development of diagnostic test carried out identifying the characteristics of diagnostic test items and measuring the percentage of students perception of the three tier diagnostic test using microsoft excel. The Research and Development (R&D) with the Borg & Gall was used in this research. It was simplified into 7 steps, namely data collection, planning, product design, testing in a small scale, revision, testing in a large scale, and final product revision. The three-tier diagnostic test has 28 items of multiple choice questions accompanied by a choice of reasons and level of confidence. The diagnoctic test involved 32 students is small scale trials and 88 students in the large scale trials. Based on data analysis, diagnostic test developed is suitable to use based on the characteristics of having high content validity of 0.77, item validity is 24 valid questions, high reliability of 0.778, low difficulty level and readability level â‰¥ 6 that is 7.55 . The perception of students in this test is 83.10%. Thus, three tier diagnostic test questions that are suitable to use are 24 question out of 28 question planned.Â Keywords: Dynamic Fluid, Microsoft Excel, Three Tier Diagnostic TestÂ